Evaluation of S100A8/A9 and neutrophils as prognostic markers in metastatic melanoma patients under immune-checkpoint inhibition - Melzer, Yasmin F.; Fergen, Nadine L; Mess, Christian; Stadler, Julia-Christina; Geidel, Glenn; Schwietzer, Ysabel A; Kött, Julian; Pantel, Klaus; Schneider, Stefan W; Utikal, Jochen; Wladykowski, Ewa; Vidal-y-Sy, Sabine; et al. (Translational oncology, 2025)
Immune-checkpoint inhibitors (ICIs) have revolutionized melanoma treatment, yet approximately half of patients do not respond to these therapies. Identifying prognostic biomarkers is crucial for treatment decisions. Our retrospective study assessed liquid biopsies and tumor tissue analyses for two potential biomarkers: danger-associated molecular pattern (DAMP) S100A8/A9 and its source, neutrophils. In 43 metastatic unresected stage III/IV melanoma patients, elevated serum levels of S100A8/A9 and neutrophils before and during ICI treatment correlated with worse outcomes. Furthermore, in 113 melanoma patients, neutrophil expression in the tumor microenvironment (TME) was associated with relapse and reduced survival. Measuring S100A8/A9 and neutrophils could enhance immunotherapy monitoring by predicting impaired clinical outcomes and non-response to ICIs. Serum S100A8/A9 levels and neutrophil counts at baseline (T0) and during treatment (T3) correlated with reduced progression-free survival (PFS). Elevated S100A8/A9 levels at T0 and T3 negatively impacted overall survival (OS). Notably, neutrophil infiltration was more prevalent in primary melanomas than in nevi and metastases, and its presence in primary melanomas was linked to poorer survival. S100A8/A9 serum levels, neutrophil counts, and tumor-associated neutrophil infiltration represent promising biomarkers for predicting treatment response and clinical outcomes in melanoma patients receiving ICIs. - Significance - These findings underscore the critical need for reliable biomarkers in melanoma research, particularly for predicting responses to immune-checkpoint inhibitors (ICIs). Identifying S100A8/A9 levels and neutrophil infiltration as potential indicators of treatment outcomes offers valuable insights for personalized therapy decisions. By enhancing monitoring and prognosis assessment, these biomarkers contribute to refining treatment strategies, ultimately improving patient care and outcomes. This research bridges gaps in understanding melanoma response mechanisms and highlights avenues for further investigation into immune-related markers, fostering advancements in precision medicine for melanoma patients.